Pedagogical conditions of professional competence formation of future biology teachers in the process of integration of disciplines - Fursa, Irina Valeriyivna (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2016)
Introduction. In the process of professional competence formation, an important place belongs to pedagogical conditions conducive to the formation of the investigated phenomenon. They determine the need of coverage of outer and inner sides of the process of students training for effective implementation of the integration processes in education. Purpose – justification of the proposed pedagogical conditions of biology teachers training with regard to integration processes in biological education. Results. Proposed pedagogical conditions of the studied phenomenon is perceived as a complex of certain interrelated components (conceptual, technological, managerial-organizational, technical and the like) that contribute to the effectiveness of training. Teaching conditions include the factors which naturally affect the process of formation of professional training of future teachers of biology and peculiarities of scientific and pedagogical disciplines: the creation of modern educational-professional programs with a focus on the integration of scientific and pedagogical disciplines; the use of different types of interdisciplinary connections in the process of future biology teachers training, creation of integrated courses of educational disciplines; integration of modern technologies of training into a single system for integrative and subject-specific training; orientation of students when undertaking independent work to perform integrative tasks in different subjects. Implementation of pedagogic conditions in practice of work of higher educational establishments involves the development of relevant educational programmers that define the requirements for the educational level of the biological profile for the program, structural and logical scheme of the study and the expected learning outcomes. Originality. Proposed author's definition of pedagogical conditions and justified their varieties, which are crucial in the process of professional training of biology teachers. Conclusion. The process of professional competence formation of future biology teachers are determined by the complex of the pedagogical conditions, which takes into account the integration of scientific and pedagogical disciplines. Further research is advisable to send in substantiation of technological component of realization of pedagogical conditions.